Phone Transcriptions (PT) Vs Google Translate Sound In Improving Students’ Pronounciations: Students’ Perceptions - Ardina Khairunnisa; Nisa Fahria Nasution; Yani Lubis (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This artical is motivateid by Phone Transcriptions or Google Translate Sound in mproving Students’ Pronountions: Students’ Perceptions. Therefore, to improve students’ pronunciation skills, the teacher suggests to students use Phone Transcriptions or Google Translate Sound as media to learn pronunciation independently. The aim of this research is to describe the students’ perceptions of using Phone Transcriptions or Google Translate Sound and to describe the obstacles do students find using Phone Transcriptions or Google Translate Sound as media in learning pronunciation. This research used qualitative method in specific descriptive qualitative methods. The participant of this research were 36 students of English Department. They are students from TBI1 in state Islamic University of North Sumatra. The result of this research shows the students’ perception on using Phone Transcriptions or Google Translate Sound as media in learning pronunciation was positive, because students can learn practically and independently.